PENGARUH PENDAPATAN PREMI, BEBAN KLAIM, RISK BASED CAPITAL DAN HASIL INVESTASI TERHADAP LABA PERUSAHAAN ASURANSI UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN INDONESIA - Agustina, Monika; Muzahid, Mukhlisul; Mukhlis, Mukhlis (Politeknik Negeri Lhokseumawe, 2024)
Abstract: Corporate Profit or commonly called profitability, is a measure of how well a company has succeeded in generating net profit from its operations in a certain period. This study aims to determine how much influence Premium Income, Claim Expenses, Risk Based Capital and Investment Returns have on the Profit of Sharia General Insurance Companies registered with the Indonesian Financial Services Authority, with an observation period of three years, namely from 2020 to 2022. The data used in this study are secondary data that are quantitative in nature, namely by using financial reports published by the Financial Services Authority. The population in this study were 25 issuers and the sample selected in this study were 17 issuers, and using the purposive sampling method with certain criteria. The analysis method uses the panel data regression analysis method. The model used in this study is the panel data fixed effect model, classical assumption test and hypothesis test. The results show that premium income, claim expenses, risk based capital and investment returns simultaneously have a significant effect on the Profit of Sharia General Insurance Companies registered with the Indonesian Financial Services Authority. Premium income partially has a negative and significant effect on company profits. Claim expenses partially have a positive and significant effect on company profits. Risk based capital partially has a positive and significant effect on company profits. Investment results partially have no effect on company profits. Keywords: Premium Income, Claims Expense, Risk Based Capital, Investment Results and Company Profit